Effect of different implant abutment surfaces on OBA-09 epithelial cell adhesion - Rigolin, Maria Sílvia M. [UNESP]; de Avila, Erica Dorigatti [UNESP]; Basso, Fernanda G. [UNESP]; Hebling, Josimeri [UNESP]; de S. Costa, Carlos Alberto [UNESP]; Mollo Junior, Francisco de Assis [UNESP] (Wiley, 2017)
For the long-term success of implants, it is necessary to achieve a direct contact between the implant and the subjacent bone. To avoid bacterial penetration that could adversely affect the initial wound healing as well as the long-term behavior of the implants, an early tissue barrier must form that is able to protect the biological peri-implant structures. Given the need of an effective tissue early barrier around dental implants, the present study evaluated, in vitro, the influence of physical and chemical characteristics of two implant abutment surfaces on gingival epithelial cells (OBA-9) adhesion. To this end, titanium (Ti) and zirconia (ZrO2) disk-shaped specimens were used mimicking the abutment components surfaces, while bovine enamel (BE) and glass cover slips (GCS) disks served as positive and negative controls, respectively. Roughness and surface free energy (SFE) of all materials were evaluated previously to cellular adhesion step. In sequence, the effect of each material on cells morphology and viability was analyzed after 1 and 24 hr. The results showed that roughness and SFE had no effect on the cell viability data or on their interaction (p =.559), independent of a post-contact analysis of 1 or 24 hr. However, cells attachment and spreading increased after 24 hr on Ti and ZrO2 than BE, corresponding to the highest SFE values. SFE appears to be an important property interfering on the quality of the soft tissue surrounding dental implants. These data can be considered a trigger point for developing new material surfaces.
Keywords: epithelial cells; implant abutment; titanium; zirconia